IMMOBILIZATION OF TIO2 ON THE SURFACE OF POLYPROPYLENE GRANULAR POLYMER AND ITS APPLICATION AS THE PHOTOCATALYST ON THE METHYLENE BLUE PHOTODEGRADATION - ALIAH , HASNIAH
Pollution of water bodies by industrial waste like textile dyes or other sources has become one of the environmental problems that require treatment. The photocatalysis techniques using semiconductor materials such as titanium dioxide (TiO2) which is activated by light is seen as an economical method to solve this problem. Moreover, the catalyst modifications are required so that after treatment ends, we do not need a complex separation technique. The modifications were done through the immobilization of catalysts on the surface of the buffer material which is lightweight, transparent and thermoplastic, by thermal milling technique. The density and the transmittance are two main parameters of polymer-coated catalyst that play an important role in dye waste degradation. Modification of milling equipment which is integrated with temperature and time controller has done to control the density and the transmittance of polymer-coated catalyst. Immobilization processes were conducted by coat the surface of thermoplastic polymer with the anatase TiO2 in technical phase. Furthermore, photodegradation process was observed in the decomposition of methylene blue (MB) solution with polymer-coated TiO2 catalyst under sunlight irradiation. As the preliminary researches, we have performed two kinds of modifications for thermal milling system, that is modifications by adding a series of heating to the milling cylinder and modification of milling cylinder-based electrical oven. The addition of the heating circuit on the milling cylinder can not ensure immobilization process takes place with a constant temperature. In addition, it takes a long time for any process of immobilization. Using milling cylinder-based electric oven repair the temperature control system. For other reason, it needed a fairly short time for each milling process. Thus, we used a technique based milling thermal electric oven in subsequent experiments. The selection of buffer material for catalyst have been done on three types of thermoplastic granular polymers, namely polystyrene (PS), linear low-density polyethylene (LLDPE) and polypropylene (PP). Heating in these processes are carried out around the point of HDT for each polymer. Based on the density and the transmittance of polymers after coating by temperature of 100 °C for 60 minutes, the PP polymers become the best buffer material for TiO2 particles with the density and the transmittance respectively of 0,872 g/cm3 and 58 %. The process of immobilization of catalysts on the surface of the polymer was carried out by superimposing the TiO2 on the surface of PP polymers with varying of milling operation parameters (temperature and of milling time). Changes in the density and transmittance then be reviewed to predict the optimum operating parameters of milling in the fabricating of polymer-coated catalysts that used in the methylene blue (MB) photodegradation. Photodegradation test was conducted to determine the effect of catalyst parameters, namely the amount of the catalyst-coated the polymer layer on the surface of the test solution, the temperature and duration of milling on the MB photodegradation. MB photodegradation indicated by reducing the concentration of MB in the test solution. The results indicate that two layers of TiO2 coated grains give the optimum decomposition rate of the MB solution. The milling temperature of 100°C and milling period of 90 minutes produced the optimum decomposition rate. The length of time of photodegradation processes also influence the physical and chemical properties of MB solutions. Increasing in the exposure time was followed by reducing in the waste color to became clear solution, also indicated the reduction in the MB concentration. After five days exposure, the concentration of MB reduced by 99,5%. Exposure duration influence on the chemical bonding characteristics of the MB compounds. Increasing the exposure time caused the increase in the concentration of hydroxyl radical OH in the solution MB. This is confirmed by the increase in pH. In this research has also tested the stability of coating products. To investigate the stability of the catalyst, photodegradation test was repeated several times using the same catalyst-coated polymer. the catalyst used at the fifth repletion was able to decompose the MB compounds up to 97% of the initial concentration. The photocatalyst material which is fabricated in this study has great potential for use in the organic wastewater treatment in large scale in tropical climates using sunlight. In addition, this technique does not require complicated handling in the process of separating the catalyst from treated water, so it can be reduce operating costs. More than that, these become an alternative catalyst material that is reusable to decompose MB solutions or other organic pollutants.